2015
DOI: 10.4103/0972-9941.140210
|View full text |Cite
|
Sign up to set email alerts
|

I-gel as an alternative to endotracheal tube in adult laparoscopic surgeries: A comparative study

Abstract: BACKGROUND:The tracheal tube is always considered to be the gold standard for laparoscopic surgeries. As conventional laryngoscopy guided endotracheal intubation evokes significant hypertension and tachycardia, we have used I-gel, second generation extraglottic airway device, in an attempt to overcome these drawbacks. We conducted this study to compare haemodynamic changes during insertion, efficacy of ventilation, and complications with the use of I-gel when compared with endotracheal tube (ETT) in laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
4
14
1
2
Order By: Relevance
“…Although tracheal intubation is considered as an ideal approach, it has disadvantages like raised respiratory and hemodynamic responses during intubation, pneumoperitoneum and extubation (3)(4)(5)(6)(7)(8)(9) . However, supraglottic airway devices (SAD) with facility for gastric suction such as Proseal LMA and I gel have been successfully used in laparoscopic cholecystectomy (10)(11)(12)(13)(14)(15)(16) . Initial experience with Baska mask has demonstrated it to be a suitable device (17,18) and there are only limited literature comparing these devices, so we decided to assess the efficiencies of Baska mask, I gel and Proseal LMA during laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Although tracheal intubation is considered as an ideal approach, it has disadvantages like raised respiratory and hemodynamic responses during intubation, pneumoperitoneum and extubation (3)(4)(5)(6)(7)(8)(9) . However, supraglottic airway devices (SAD) with facility for gastric suction such as Proseal LMA and I gel have been successfully used in laparoscopic cholecystectomy (10)(11)(12)(13)(14)(15)(16) . Initial experience with Baska mask has demonstrated it to be a suitable device (17,18) and there are only limited literature comparing these devices, so we decided to assess the efficiencies of Baska mask, I gel and Proseal LMA during laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Badheka noticed that the time required for I-gel insertion was significantly less when compared with ETT. 8,9 Shi YB et al, noticed that the insertion time, sealing pressure and incidence of sore throat was lower with I-gel than with proseal LMA and LMA supreme. 10 Abdel aziz et al, found that the insertion time was significantly shorter in the I-gel group, but oropharyngeal seal was better with Baskamask.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the gastric channel in i-gel provides protection against aspiration. Hence, i-gel can be a safe and suitable alternative to ETT [7].…”
Section: Discussionmentioning
confidence: 99%